Synthesis and antiproliferative evaluation of novel 2-(4H-1,2,4-triazole-3-ylthio)acetamide derivatives as inducers of apoptosis in cancer cells - ÖZSAVCI, DERYA; TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY; KULABAŞ, NECLA; BİNGÖL ÖZAKPINAR, ÖZLEM (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2016)
In this study, a series of thiosemicarbazide derivatives 12-14, 1,2,4-triazol-3-thione derivatives 15-17 and compounds bearing 2-(4H-1,2,4-triazole-3-ylthio)acetamide structure 18-32 have been synthesized starting from phenolic compounds such as 2-naphthol, paracetamol and thymol. Structures and purity of the target compounds were confirmed by the use of their chromatographic and spectral data besides microanalysis. All of the synthesized new compounds 12-32 were evaluated for their anti-HIV activity. Among these compounds, three representatives 18, 19 and 25 were selected and evaluated by the National Cancer Institute (NCI) against the full panel of 60 human cancer cell lines derived from nine different cancer types. Antiproliferative effects of the selected compounds were demonstrated in human tumor cell lines K-562, A549 and PC-3. These compounds inhibited cell growth assessed by MTT assay. Compound 18,19 and 25 exhibited anti-cancer activity with IC50 values of 5.96 mu M (PC-3 cells), 7.90 mu M (A549/ATCC cells) and 7.71 mu M (K-562 cells), respectively. After the cell viability assay, caspase activation and Bcl-2 activity of the selected compounds were measured and the loss of mitochondrial membrane potential (MMP) was detected. Compounds 18, 19 and 25 showed a significant increase in caspase-3 activity in a dose-dependent manner. This was not observed for caspase-8 activity with compound 18 and 25, while compound 19 was significantly elevated only at the dose of 50 mu M. In addition, all three compounds significantly decreased the mitochondrial membrane potential and expression of Bcl-2. (C) 2016 Elsevier Masson SAS. All rights reserved.
Keywords: 1,2,4-Triazoles; Thioethers; Anticancer activity; Apoptosis; Caspase-3; Caspase-8; Bcl-2; ANTICANCER DRUG SCREEN; 1,2,4-TRIAZOLE DERIVATIVES; ANTIINFLAMMATORY ACTIVITY; REVERSE-TRANSCRIPTASE; BIOLOGICAL EVALUATION; COLORIMETRIC ASSAY; ANTITUMOR-ACTIVITY; PROSTATE-CANCER; INHIBITORS; AGENTS